Preparation and characterization of novel anti-inflammatory biological agents based on piroxicam-loaded poly-ε-caprolactone nano-particles for sustained NSAID delivery. (1st January 2020) - Rahmani Del Bakhshayesh, Azizeh; Akbarzadeh, Abolfazl; Alihemmati, Alireza; Tayefi Nasrabadi, Hamid; Montaseri, Azadeh; Davaran, Soodabeh; Abedelahi, Ali
Abstract: Piroxicam (PX), a main member of non-steroidal anti-inflammatory drugs (NSAIDs), is mainly used orally, which causes side effects of the gastrointestinal tract. It also has systemic effects when administered intramuscularly. Intra-articular (IA) delivery and encapsulation of PX in biodegradable poly-ε-caprolactone (PCL) nanoparticles (NPs) offer potential advantages over conventional oral delivery. The purpose of this study is the development of a new type of anti-inflammatory bio-agents containing collagen and PX-loaded NPs, as an example for an oral formulation replacement, for the prolonged release of PX. In this study, the PX was encapsulated in PCL NPs (size 102.7 ± 19.37 nm, encapsulation efficiency 92.83 ± 0.4410) by oil-in-water (o/w) emulsion solvent evaporation method. Nanoparticles were then characterized for entrapment efficiency, percent yield, particle size analysis, morphological characteristics, and in vitro drug release profiles. Eventually, the NPs synthesized with collagen were conjugated so that the NPs were trapped in the collagen sponges using a cross-linker. Finally, biocompatibility tests showed that the anti-inflammatory agents made in this study had no toxic effect on the cells. Based on the results, it appears that PX-loaded PCL NPs along with collagen (PPCLnp-Coll) can be promising for IA administration based on particulate drug delivery for the treatment of arthritis.